PREPARATION AND THERMAL-DECOMPOSITION OF SOLID-STATE COBALT, NICKEL, COPPER AND ZINC CHELATES OF ETHYLENEDIAMINETETRAACETIC ACID - Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Ionashiro, Massao [UNESP] (Elsevier B.V., 1993)
Solid state chelates of general formula H-2[M(EDTA)] . nH2O, where M is Co, Ni, Cu or Zn, and EDTA is ethylenediaminetetraacetate, were prepared. Thermogravimetry-derivative thermogravimetry (TG-DTG), differential thermal analysis (DTA) and complexometry were used to characterize and to study the thermal stability and thermal decomposition of these compounds.